A new species of satyrine butterfly from Patagonia in more than a century and revisional notes on the genus Faunula C. Felder & R. Felder (Lepidoptera: Nymphalidae: Satyrinae) - Pyrcz, Tomasz W. (Zootaxa, 2012)
A new species of Satyrinae butterfly, Faunula dubii n. sp., is described from southern Patagonia in Chile and Argentina.Its affinities with other species of the genus Faunula C. & R. Felder are evaluated, and its distribution and habitat arediscussed. A new combination Faunula euripides n. comb., and a new synonymy are proposed, Punargenteus penaiHayward n. syn. of Satyrus gustavi (Staudinger). Generic status of Chillanella stelligera (Butler) is reconsidered. All the species of Satyrinae occurring in southern Patagonia are listed.